Transition-Metal-Catalyzed Cross-Coupling of Chlorosilanes - Yang, Ying-Hui; Pang, Xiaobo; Shu, Xing-Zhong (Synthesis, 2022)
Chlorosilanes are the most accessible feedstock chemical in the organosilicon world. Cross-coupling involving chlorosilanes by transition metal catalysis offers a promising way for the production of organosilanes, which play essential roles in many important research areas, including agriculture, medicinal chemistry, and material science. This chemistry is firstly realized by coupling chlorosilanes with organometallic species and then extended to the silyl-Heck reaction with alkenes. Very recently, the cross-electrophile coupling of chlorosilanes has also been established. In this review, we summarize the progress of this chemistry.1 Introduction2 Cross-Coupling of Chlorosilanes with Organometallic Reagents3 The Silyl-Heck Reaction of Chlorosilanes and Alkenes4 Reductive Cross-Coupling of Chlorosilanes with Electrophiles5 Summary and Outlook
Keywords: organosilanes; chlorosilanes; cross-coupling; silylation; nickel; synthetic methodology